2022
DOI: 10.3390/diagnostics12020308
|View full text |Cite
|
Sign up to set email alerts
|

An Antibody-Aptamer-Hybrid Lateral Flow Assay for Detection of CXCL9 in Antibody-Mediated Rejection after Kidney Transplantation

Abstract: Chronic antibody-mediated rejection (AMR) is a key limiting factor for the clinical outcome of a kidney transplantation (Ktx), where early diagnosis and therapeutic intervention is needed. This study describes the identification of the biomarker CXC-motif chemokine ligand (CXCL) 9 as an indicator for AMR and presents a new aptamer-antibody-hybrid lateral flow assay (hybrid-LFA) for detection in urine. Biomarker evaluation included two independent cohorts of kidney transplant recipients (KTRs) from a protocol b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Importantly, the greater concentration of CXCL9 portends improved laboratory test characteristics, and CXCL9 has the potential to be included in existing platforms in clinical laboratories or developed as a point-of-care test. In fact, point-of-care devices identifying CXCL9 are currently under development for diagnosis of acute cell-mediated transplant rejection, which, similar to AIN, is a tubulointerstitial immune-mediated process that spares the glomeruli, and such devices could be adapted for rapid, bedside diagnosis of AIN ( 30 ). Our findings also provide insight into AIN pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the greater concentration of CXCL9 portends improved laboratory test characteristics, and CXCL9 has the potential to be included in existing platforms in clinical laboratories or developed as a point-of-care test. In fact, point-of-care devices identifying CXCL9 are currently under development for diagnosis of acute cell-mediated transplant rejection, which, similar to AIN, is a tubulointerstitial immune-mediated process that spares the glomeruli, and such devices could be adapted for rapid, bedside diagnosis of AIN ( 30 ). Our findings also provide insight into AIN pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study [ 24 ] concludes that uNGAL may be more helpful in assessing renal function in the first week after KT when combined with other markers. Another study found that NGAL levels in urine and serum could be used to predict kidney damage and as a biomarker of acute kidney injury after transplantation [ 28 ]. According to the researchers, patients with acute kidney injury had higher uNGAL levels than patients without acute kidney injury, with a 2 h post-transplant increase.…”
Section: Serological and Urine Biomarkersmentioning
confidence: 99%
“…In the literature, this sensing strategy has also been combined with duplex aptamers, where the labelled duplex aptamers were disassociated from their complementary In addition, some studies were designed to combine antibodies and aptamers in a single hybrid LFA. In such an example, CXC-motif chemokine ligand (CXCL) 9 (a critical urinal biomarker for antibody-mediated rejection of kidney transplantation) was detected on a tracking sandwich format LFA [57]. Antibodies specific to CXCL 9 were initially utilized as capture probes on the test line, and the detection aptamers specific to CXCL 9 were conjugated to AuNPs to ensure signal transduction.…”
Section: Paper-based Colorimetric Aptasensorsmentioning
confidence: 99%